Analisis Metode Split Tensile Test Komposit Laminat Jute Terhadap Kekuatan Tarik Belah Beton Kolom Silinder - Hidayat, Nurul; Jusuf Zulfikar, Achmad; Iswandi, Iswandi (CV. IRA PUBLISHING, 2022)
Composite materials have experienced quite rapid development as new alternative materials to replace metal materials. The concrete structure is the main structure of a building and will experience a decrease in its mechanical strength over time. In this study, laminated composite materials from woven jute fabrics will be used as reinforcement for concrete structures. The purpose of this study was to obtain the tensile strength of cylindrical column concrete (BKS) reinforced by laminated jute composite (KLJ) using the split tensile test method, to analyze the validity of the test results using the normally distributed data method (DTN), and to analyze the tensile strength of BKS reinforced KLJ based on test results of the split tensile test method. The split tensile test uses the ASTM C496 standard with a variety of layers from 1 layer to 4 layers of KLJ. Each variation was tested 3 times. KLJ casing printing on BKS uses the Vacuum Bagging method. As a comparison, 3 specimens without KLJ casing were prepared as control specimens. The results of the investigation showed that the application of the KLJ sheath to the BKS resulted in an increase in the split tensile strength of the BKS at 1, 2, 3, and 4 KLJ sheaths by 62%, 166%, 200%, and 330% respectively. Thus, the provision of a KLJ sheath has the potential to strengthen the BKS structure.